OPTIMIZING SILICON APPLICATION TO IMPROVE SALINITY TOLERANCE IN MAIZE (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Salinity often suppresses the wheat performance. As wheat is designated as silicon (Si) accumulator, hence Si application may alleviate the salinity induced damages. With the objective to combat the salinity stress in wheat by Si application  (0,  50,  100,  150  and 200  mg L-1) using calcium silicate, an experiment was conducted on  two contrasting wheat genotypes (salt sensitive; Auqab-2000 and salt tolerant; SARC-5) in salinized (10 dS m-1) and non-salinized (2 dS m-1) solutions. Plants were harvested 32 days after transplanting and evaluation was done on the basis of dferent morphological and analytical characters. Silicon supplementation into the solution culture improved wheat growth and K+/Na+ with reducedNa+  and enhanced K+  uptake. Concomitant improvement in shoot growth was observed; nonetheless  the root growth remained unaffected by Si application. Better results were obtained with 150 and 200 mg L-1 of Si which were found almost equally effective. It was concluded that SARC-5 is better than Auqab-2000 against salt stress and Si inclusion into the solution medium is beneficial for wheat and can improve the crop growth both under optimal and salt stressful conditions.